Overcoming Challenges in Digital Public Service Delivery: Insights from Lapak Aduan Implementation - Etin Indrayani; Fergie Akbar; Suhajar Diantoro (Institut Pemerintahan Dalam Negeri, 2025)
The Banyumas Regency Government provides services to the community and establishes interactive government and public services through a public communication space called